Perancangan Interior Kafe Basillico Pada Hotel Senggigi Beach di Lombok - Fipthi Nopiliansa (Intra, 2013)
Interior design cafe Basillico in Lombok is a commercial facility design projects that can support the level of tourism for a trip to Lombok. Basillico cafe where design will also reflect the culture of the island of Lombok, so that the visitors can enjoy the natural charm than dishes on offer and can also know the culture of Lombok unique and interesting, from diverse cultural arts Lombok. While the design concept cafe itself Basillico applying traditional concepts and philosophy of traditional buildings and art Lombok. Therefore, in the design of the cafe is using the theme Identity of Traditional Lombok, so the design of this cafe many uses materials such as wood in order to reinforce the design theme. The design and use a lot of broken formations as dominant, tekas lines and solid circles are applied to each room, so that the unity and attractive in terms of aesthetics and functionality.